Alienation Effects : Performance and Self-Management in Yugoslavia, 1945-91 - Jakovljević, Branislav (Book collections on Project MUSE., 2016)
Exciting new scholarship has been emerging as performance studies scholars begin to turn their attention to the performance of politics, nationhood, and jurisprudence. Branislav Jakovljevic's project on the history and eventual demise of the former Yugoslavia demonstrates how fruitful this approach can be. Jakovljevic considers the concept of theatricality as central to understanding the events that took place in Yugoslavia. He examines the country's trials, state ceremonies and festivals, army maneuvers, propaganda, and pop culture as "rehearsals and temporary enactments of an ideologically formulated future." His first chapter reveals the surrealist, avant-garde origins of key members of the Yugoslav bureaucracy after WWII, suggesting that those connections helped the culture of socialist Yugoslavia become a performance-centered culture. Continuing to explore the relationship between the political avant-garde and the artistic avant-garde, he looks at the spectacle of student demonstrations in Belgrade in 1968, and, in their aftermath, the rise of performance art in the country. The third chapter (included here) zeros in on the various political performances of Slobodan Milosevic, including his courtroom testimony at the ICTY, the International Criminal Tribunal for the former Yugoslavia. The fourth chapter discusses the "Peter Handke Affair," when the Austrian playwright had a major prize revoked after he attended Milosevic's funeral and recited a poem he had written in Milosevic's honor